PENGARUH KEPUASAN KERJA, DISIPLIN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT. PACIFIC EXPRESS CARGO, DENPASAR, BALI - Ni Kadek Purnama Dewi; Gde Bayu Surya Parwita; Ni Made Dwi Puspitawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
In today's dynamic world of work, work is increasingly being done in teams, and flexibility is very important. Organizations really need employees who are able to display good performance. There are problems that occur at PT. Pacific Express Cargo, namely that there are still employees who do not arrive on time, often leave their workplace without permission, and are indifferent in serving customers. This behavior is an action that does not support effectiveness and efficiency in work. This research was conducted with the aim of determining the impact of job satisfaction, work discipline, and work stress on the performance of PT employees. Pacific Express Cargo. The population used in this research was all employees of PT Pacific Express Cargo, totaling 40 people. The sampling method used in this research was a saturated sample. The data analysis technique used in this research is multiple linear regression analysis. The results of the analysis show that (1) job satisfaction has a positive and significant effect on the performance of PT employees. Pacific Express Cargo: (2) Work discipline has a positive and significant effect on the performance of PT employees. Pacific Express Cargo: (3) Work stress has a negative and significant effect on the performance of PT employees. Pacific Express Cargo.